A1.1 Anti-Citrullinated Protein Antibody Specific Fc Glycosylation Patterns in Arthralgia Patients. (25th February 2013) - Kempers, AC; Scherer, HU; Rombouts, Y; Ewing, E; Stadt, LA van de; Selman, MHJ; Deelder, AM; Huizinga, TWJ; Wuhrer, M; Schaardenburg, D van; Toes, REM
Abstract : Background/Objectives: During rheumatoid arthritis, anti-citrullinated protein antibodies (ACPA) exhibit a specific, pro-inflammatory Fc glycosylation profile that is characterised by a low content of galactose and sialic acid residues. The absence of these sugars from the Fc-linked core glycan could influence the biological activity of ACPA during disease. As ACPA can be detected in sera several years before disease development, we hypothesised that a change in ACPA Fc-glycosylation might precede the onset of arthritis. Methods: Serum samples (n = 300) of patients with ACPA positive arthralgia (n = 184) were obtained at various time points. In this cohort, 96 patients developed arthritis after an average duration of 14.7 months of arthralgia. At the time of the onset of arthritis, patients were defined as having rheumatoid arthritis (RA, n = 51) based on the 1987 ACR criteria for RA, or undifferentiated arthritis (UA, n = 45). ACPA were isolated from serum samples by affinity purification, using cyclic citrullinated peptides as antigen. Purified ACPA-IgG and total serum IgG were digested with trypsin and resulting IgG1 Fc glycopeptides were analysed by mass spectrometry. Results: No significant change in Fc-glycosylation patterns was found between ACPA-specific and total serum IgG1 at the patients' first presentation with arthralgia (baseline). However, at diagnosis of arthritis, RA patients but not patients with UA exhibited increased hypogalactosylation of the ACPA and total IgG Fc fragments compared to healthy donors. The decrease of ACPA galactosylation levels at the Fc-tail occurred at 6 months before diagnosis and was significantly more pronounced at 3 months before diagnosis compared to total IgG. Conclusions: A decrease in Fc-galactosylation levels of ACPA occurred around 6 months prior to RA onset. Of interest, this ACPA hypogalactosylation was more pronounced than that of total IgG1, indicating that a more pro-inflammatory Fc-glycosylation pattern could be one mechanism driving inflammation in RA.